Stabilizing Perovskite Precursor by Synergy of Functional Groups for NiOx‐Based Inverted Solar Cells with 23.5 % Efficiency. Issue 35 (13th July 2022) - Li, Mengjia; Li, Haiyun; Zhuang, Qixin; He, Dongmei; Liu, Baibai; Chen, Cong; Zhang, Boxue; Pauporté, Thierry; Zang, Zhigang; Chen, Jiangzhao
Abstract: Perovskite solar cells suffer from poor reproducibility due to the degradation of perovskite precursor solution. Herein, we report an effective precursor stabilization strategy via incorporating 3‐hydrazinobenzoic acid (3‐HBA) containing carboxyl (−COOH) and hydrazine (−NHNH2 ) functional groups as stabilizer. The oxidation of I −, deprotonation of organic cations and amine‐cation reaction are the main causes of the degradation of mixed organic cation perovskite precursor solution. The −NHNH2 can reduce I2 defects back to I − and thus suppress the oxidation of I −, while the H + generated by −COOH can inhibit the deprotonation of organic cations and subsequent amine‐cation reaction. The above degradation reactions are simultaneously inhibited by the synergy of functional groups. The inverted device achieves an efficiency of 23.5 % (certified efficiency of 23.3 %) with an excellent operational stability, retaining 94 % of the initial efficiency after maximum power point tracking for 601 hours. Abstract : A precursor stabilization and defect passivation strategy was developed by employing 3‐hydrazinobenzoic acid (3‐HBA) as a versatile additive. The synergistic effect of −NHNH2 and −COOH suppresses oxidation of I −, deprotonation of organic cations and amine‐cation reaction. The NiO x ‐based inverted device achieves a certified efficiency of 23.3 % with excellent operational stability.